2021
DOI: 10.1038/s41565-021-00870-y
|View full text |Cite
|
Sign up to set email alerts
|

Computationally guided high-throughput design of self-assembling drug nanoparticles

Abstract: Nanoformulations are transforming our capacity to effectively deliver and treat a myriad of conditions. However, many nanoformulation approaches still suffer from high production complexity and low drug loading. One potential solution relies on harnessing co-assembly of drugs and small molecular excipients to facilitate nanoparticle formation through solvent exchange without the need for chemical synthesis, generating nanoparticles with up to 95% drug loading. However, there is currently no understanding which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…From these screens, "laws" on structure-function relationships can be extracted through computational modeling methods, including machine learning. [128,129] To close the clinical translation gap, large animal models are highly valuable. For example, Binderup et al showed, in 2019, that producing and evaluating A1-nanotherapeutics is scalable from mice to larger animals, i.e., rabbits and porcine cardiovascular disease models.…”
Section: Discussionmentioning
confidence: 99%
“…From these screens, "laws" on structure-function relationships can be extracted through computational modeling methods, including machine learning. [128,129] To close the clinical translation gap, large animal models are highly valuable. For example, Binderup et al showed, in 2019, that producing and evaluating A1-nanotherapeutics is scalable from mice to larger animals, i.e., rabbits and porcine cardiovascular disease models.…”
Section: Discussionmentioning
confidence: 99%
“… 137–139 In another example, the integration of high-throughput experimentation with machine learning led to the identification of 100 drug NPs with high loading capacity. 140 In addition, the use of machine learning tools can be envisioned as a strategy to identify new principles for more efficient release 141 and targeting 135 to specific cells.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…rapidly screened through 1440 pairings of drugs and excipients for co-aggregation into nanoparticles by using a combination of liquid handling and high throughput dynamic light scattering characterization ( Fig. 6 ) [ 53 ]. A random forest machine learning model was used to gain insight into the molecular features for co-aggregation, and subsequently used to predict additional co-aggregators (1.8%) from 2.1 million possible pairings of FDA approved drugs and excipients.…”
Section: Nanoengineered Biomaterials Applicationsmentioning
confidence: 99%
“…(e) The machine learning model was used to model 2.1 million pairs of drugs and excipients for ability to co-aggregate and form nanoparticles, and the six named pairs were validated experimentally. The novel component that was not part of the initial high throughput screen in part A are underscored [ 53 ]. …”
Section: Nanoengineered Biomaterials Applicationsmentioning
confidence: 99%